Mortality Rate and Related Risk Factors in Hospitalized Coronavirus Disease 2019 Patients with Diabetes: A Single-Center Study: - Aryan, Hoda; Najmaldin, Atousa; Gohari, Ali (Galen Medical Journal, 2022)
Background: The outbreak of the new coronavirus disease 2019 (COVID-19) is majorly threatening the health of people worldwide. Since patients with chronic diseases, including diabetes mellitus (DM), are among the main groups at risk of severe COVID-19; hence, this study was aimed to investigate the mortality rate of COVID-19 among patients with DM. Materials and Methods: This cross-sectional study was performed on 211 DM patients with COVID-19 who were referred to Educational Kowsar Hospital in Semnan, Iran. After a definitive diagnosis of COVID-19, basic characteristics, including gender, weight, height, and clinical information (such as initial signs and symptoms, underlying diseases, complications during hospitalization, and type of treatment received) were collected. Results: The mean age of patients was 64.92Â±12.7 years, and 51.7% were male. Totally 20.9% of patients were expired. The most frequent underlying diseases were hypertension and ischemic heart disease. The simultaneous presence of cardiovascular diseases in DM patients with COVID-19 was correlated with a considerable mortality rate increment. Cough on arrival significantly predicted mortality reduction to less than one-third (P=0.009). Also, oxygen saturation of less than 90% on arrival was a significant predictor of an increase in mortality by more than double (P<0.001). Conclusion: According to the results of multivariate logistic regression, it was found that DM can increment the probability of contracting COVID-19, and the rate of mortality was also higher in these patients.